Analysis of LT and ST Genes of Enterotoxigenic Escherichia coli Using Polymerase Chain Reaction Method in Lawar Plek from Ketewel Village, Gianyar - I Made Yogi Hardiyanta; I Gusti Agung Ayu Putu Swastini; Heri Setiyo Bekti (Borneo Scientific Publishing, 2024)
Lawar plek is a traditional Balinese dish made from raw meat, which poses a potential risk of contamination by pathogenic bacteria, including Enterotoxigenic Escherichia coli (ETEC). This study aimed to identify the presence of ETEC in lawar plek samples from Ketewel Village, Gianyar. This research uses molecular methods. The identification was conducted in two stages: initial isolation of suspected bacteria on Eosin Methylene Blue Agar (EMBA), followed by molecular confirmation using Polymerase Chain Reaction (PCR). The study results show that in EMBA culture, 4 out of 12 samples (33.33%) showed colonies presumptively identified as E. coli. However, PCR analysis revealed that none of these isolates carried the LT (heat-labile toxin) or ST (heat-stable toxin) genes characteristic of ETEC. The conclusion shows that neither the LT (heat-labile toxin) nor the ST (heat-stable toxin) virulence genes of Enterotoxigenic Escherichia coli were found in any of the samples tested as suspected Escherichia coli colonies on EMBA.